Polymers for advanced lithium-ion batteries: state of the art and future needs on polymers for the different battery components - Costa, Carlos Miguel Silva (2020)
Polymers have been successfully used as electrode compounds and separator / electrolyte materials for lithium ion batteries (LiBs) due to their inherent outstanding properties such as low-density, easy of processing, excellent thermal, mechanical and electrical properties and easily tailored functional performance matching the final device requirements. Battery performance strongly depends on the polymer type used. The physico-chemical properties of the polymers that are being used as different battery components need to be further improved to boost the development of the next generation of batteries for the electric vehicle industry, where increased energy density and safety are required. Considering its role in LIBs, this review summarizes the latest advances in the field of polymers applied as electrode compounds and separator/electrolytes. For each battery component, the state-of-art is divided by polymer type. Current bottlenecks and challenges that face polymers in LIBs are shown, and possible strategies to face them are provided.